2012
DOI: 10.1089/neu.2011.1979
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological and Behavioral Effects of Immediate and Delayed Hemorrhagic Shock after Mild Traumatic Brain Injury in Rats

Abstract: The purpose of this study was to investigate the increased susceptibility of the brain, after a controlled mild cortical impact injury, to a secondary ischemic insult. The effects of the duration and the timing of the secondary insult after the initial cortical injury were studied. Rats anesthetized with isoflurane underwent a 3 m/sec, 2.5-mm deformation cortical impact injury followed by hypotension to 40 mm Hg induced by withdrawing blood from a femoral vein. The duration of hypotension was varied from 40 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 40 publications
1
31
0
Order By: Relevance
“…2,24 Animal experiments have also demonstrated that longer durations of hypotension result in marked expansion in the brain lesion size. 25 Therefore, appropriate resuscitation is important in patients where TBI is complicated by the presence of HS. 26,27 The role of intravenous fluid therapy in prehospital trauma care is controversial.…”
Section: Discussionmentioning
confidence: 99%
“…2,24 Animal experiments have also demonstrated that longer durations of hypotension result in marked expansion in the brain lesion size. 25 Therefore, appropriate resuscitation is important in patients where TBI is complicated by the presence of HS. 26,27 The role of intravenous fluid therapy in prehospital trauma care is controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Previous clinical and experimental studies have shown that postinjury hypotension can exacerbate tissue damage. 72,73 For example, a recent study by Robertson and colleagues has reported that a 60-min period of hypotension (MAP reduced to 40 mm Hg), when initiated up to 1 h postinjury, significantly increases cortical contusion volume. 72 Although we have observed that guanabenz can cause a similar reduction in blood pressure in uninjured anesthetized animals (data not shown), both acute (30 min postinjury) and delayed (24 h postinjury) administration of 5.0 mg/kg of guanabenz reduced cortical tissue loss.…”
Section: Figmentioning
confidence: 99%
“…72,73 For example, a recent study by Robertson and colleagues has reported that a 60-min period of hypotension (MAP reduced to 40 mm Hg), when initiated up to 1 h postinjury, significantly increases cortical contusion volume. 72 Although we have observed that guanabenz can cause a similar reduction in blood pressure in uninjured anesthetized animals (data not shown), both acute (30 min postinjury) and delayed (24 h postinjury) administration of 5.0 mg/kg of guanabenz reduced cortical tissue loss. Although the longer delay did not offer significant hippocampal protection, determination of the therapeutic window may help to maximize neuroprotection while minimizing adverse influences associated with postinjury mean arterial pressure (MAP) reduction.…”
Section: Figmentioning
confidence: 99%
“…If at any point during the experiment the CPP or MABP decreased below normal autoregulatory limits (CPP < 50 mm Hg and MABP < 60 mm Hg; (Bratton et al, 2007a (http://www. braintrauma.org/coma-guidelines/); Dennis et al, 2009;Navarro et al, 2012); dashed lines Figures 1B and 1C), then the animal was excluded from analysis. Note that throughout the majority of the experiment the MABP of animals sustaining injury, irrespective of the pattern of postinjury ICP, was comparable to the sham-injured group ( Figure 1B).…”
Section: Physiological Assessment Revealed Two Injuryinduced Patternsmentioning
confidence: 99%